Presence and monitoring of albino giant anteaters (Myrmecophaga tridactyla) in the Cerrado savanna - Attias, Nina; Yogui, Débora Regina; Alves, Mario; Kluyber, Danilo; Costa, Miriã Ribeiro; Pereira da Silva, Polyana Mayume; Queiroz, Ednilson Paulino; Desbiez, Arnaud L. J. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2023)
Here we present two cases of albinism in giant anteaters from the same area in Central Brazil. The two juvenile individuals presented light-colored fur, unpigmented eyes, and pinkish skin around the eyes, ears, and snout tip. One of the individuals died before achieving adulthood. Given that albinism might affect individual behavior, survival, and fitness, we have started the GPS monitoring of one of the albino individuals. We present the results of our initial health assessment of the individual, showing that its parameters are generally within normality. We also present opportunistic observations showing that its atypical coloration did not affect intraspecific interactions, i.e., the parental care provided by its mother. Finally, we discuss the potential relationship between the individuals, how this could be related to landscape degradation and its associations with population declines in the region. Hence, these records provide additional evidence on the urgency of implementation of conservation measures to cease further population declines of giant anteaters in the Cerrado biome, here, focusing on the Mato Grosso do Sul state, Brazil.